56.4k views
5 votes
Simplify. Assume that no denominator is equal to zero.

Simplify. Assume that no denominator is equal to zero.-example-1
User Ed Mazur
by
5.6k points

2 Answers

4 votes

Answer:

c is the answer

Explanation:

All work is shown and pictured

Simplify. Assume that no denominator is equal to zero.-example-1
User Rahul Babu
by
5.9k points
0 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{(2a^7b)^2}{32b^6}\implies \cfrac{(2^2a^(7\cdot 2)b^2)}{32b^6}\implies \cfrac{4a^(14)b^2}{32b^6}\implies \cfrac{a^(14)}{8b^6b^(-2)}\implies \cfrac{a^(14)}{8b^(6-2)}\implies \cfrac{a^(14)}{8b^4}

User Elcomendante
by
5.7k points